Could calgranulins and advanced glycated end products potentiate acromegaly pathophysiology?. (June 2019) - Kruse, Colin P.S.; Cottrill, David A.; Kopchick, John J.
Abstract: Growth hormone (GH) exerts a diverse set of effects across many tissues including fat, muscle, bone, kidney, heart, and liver. GH is also a diabetogenic hormone in that it inhibits the actions of insulin. Acromegaly, a condition traditionally characterized by increased levels of growth hormone secretion as a result of pituitary adenoma, results in increased tissue growth, lipolysis, and can result in patients with hyperglycemia and hyperinsulinemia. While current treatment modalities have greatly improved prognoses for most patients, a significant number present clinical symptoms of acromegaly with elevated levels of IGF-1 in the absence of increased GH levels, a phenomenon known as micromegaly. This condition presents a challenge to most currently used treatments since the high circulating IGF-1 levels are independent of elevated levels of GH. It has been previously shown that advanced glycation end products (AGE) can stimulate IGF-1 secretion by human monocytes in vitro, demonstrating a possible mechanism for increased IGF-1 levels. To further investigate AGE/GH/IGF-1 interaction, we have reanalyzed a publicly available RNAseq dataset from subcutaneous adipose tissue of patients with acromegaly. S100A1, a member of the calgranulin family of proteins and ligand of the AGE receptor, was shown to be significantly upregulated in patients with acromegaly. These findings identify an important consideration that may help explain the counterintuitive nature of micromegaly, while simultaneously providing new insight into the role of GH in diabetic, inflammatory, and immune pathologies. Highlights: The calgranulin S100A1 shows increased expression in white adipose tissue of patients with acromegaly Calgranulin signaling mechansims overlap with GH and have been shown to induce IGF-1 expression working in concert with AGEs S100A1/AGEs may potentiate acromegaly pathophysiology and have sufficient overlap with GH action to cause abnormal pathologies.